Global studies : (Dushkin Pub. Group, 1991)
This edition includes country reports, statistics, and background essays on the Pacific Rim, the Pacific Islands, and Japan. It also features articles from newspapers and magazines from around the world, and an annotated list of World Wide Web sites, guiding students to additional resources